Continuing education in education: evolution, models and digital skills - Jaime Manzanarez, Bryan Alexander (Scientific journal of social studies, 2024)
This article explores the evolution of continuing education, highlighting its importance for the professional development of teachers in the context of rapid technological advances and social changes. A literature review analyses various theoretical models, such as TPACK, Competency-Based Learning (CBL), and others, that integrate digital, emotional, and social competencies in teacher training. The study highlights challenges in implementing continuing education, such as lack of resources, resistance to change, and variability in the quality of training programmes. NVivo software was used to systematically analyze qualitative data, identifying five key models: Wilkerson’s Triad, Kay’s TPACK, Tondeur’s SQD, and Albion et al. The results suggest an evolution, toward more complex and multidimensional approaches that recognize the interdependence of technical and pedagogical competencies with positive attitudes, toward technology. Finally, recommendations are presented to improve continuing education, emphasizing the need for institutional support, developing digital skills, and promoting a culture of continuous learning. These conclusions underline the importance of adopting adaptive strategies that respond to the changing needs of teachers and promote quality education in an increasingly digital environment.